Can hydrolytic activity of Candida strains isolated from COPD patients change with the basic disease progression? - Kuźnar, Barbara; Brajer, Beata; Batura-Gabryel, Halina; Młynarczyk, Witold (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
An increasing number of Candida infections has drawn attention to Candida ’s pathogenic features. Fungi pathogenicity, including enzymatic activity, determines the course of infection. Candida ’s hydrolytic exoenzymes play an important role in human mucosa membranes colonization by these fungi and also in their invasion. In Pulmonary Disease Clinics patients with COPD are especially susceptible to contracting Candida infection. In this group of patients (analogous to the assumed effect of bacteria which colonize bronchial tree), Candida existence may probably influence the basic disease progression for example through stimulation and supporting the chronic inflammatory process in COPD. Aims: 1. Estimation and comparison of hydrolytic activity of Candida strains isolated from COPD patients and a healthy control group. 2. Looking for correlations between hydrolytic activity of Candida and the stage of COPD (FEV1). Methods and materials: 53 patients with COPD and 14 healthy subjects from the control group took part in our study. We used their sputum induced by 4% NaCl solution. Candida strains were grown on Sabouraud’s ground and identified using ID C 32 test (bioMérieux). The hydrolytic activity of 19 enzymes was estimated in nanomoles of hydrolyzed substrate using API ZYM semiquantity test (bioMérieux). The stage of COPD was estimated according to the PTF criteria on the basis of spirometry (ABC Pneumo RS system). Results: 1. Candida strains isolated from COPD patients showed the activity of 19 enzymes and those isolated from the control group of 18 from 19 hydrolytic enzymes (no α-fucosidase activity). 2. Candida strains isolated from COPD patients showed the highest activity of secretion enzymes such as leucine arylamidase (median 3.16) and esterase lipase (median 2.96); activity of α-fucosidase (median 0.15) and α-chymotripsin (median 0.13) was the lowest. For Candida strains isolated from the control group, the activity of leucine arylamidase (median 3.64) and α-glucosidase (median 2.83) was the highest; the activity of tripsin, α-chymotripsin, α-galactosidase, ß-galactosidase and α-mannosidase (median 0.7) - the lowest. A difference that is close to significant was observed in the activity for esterase lipase - p=0.07, α-mannosidase - p=0.07, α-galactosidase - p=0.06. These hydrolytic enzymes revealed a higher activity in COPD patients. 3. We noticed positive significant correlation between FEV1 and N-acetyl-ß-glucosaminidase secretion (p=0.04; r=+0.41) in mild and moderate stages of COPD. In a group of patients with semi severe and severe COPD positive significant correlation between FEV1 and leucine arylamidase activity (p=0.02; r=+0.49) was observed; there was statistically negative significant correlation between FEV1 and ß-glucuronidase (p=0.02; r=-0.47) and ß-glucosidase (p=0.03; r=-0.47) activities. Conclusion: 1) The strong hydrolytic activity of Candida strains isolated from COPD patients proves their considerable pathogenicity. 2) The activity of several enzymes of Candida is correlated with the stage of the basic disease. 3) The above facts start a discussion about a potential influence of Candida present in human airways on the pathogenesis and on the course of COPD progression.